2008
DOI: 10.1021/jp801245h
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical and Electronic Structure Variability of the Sugar−phosphate Backbone in Nucleic Acids

Abstract: The anionic sugar-phosphate backbone of nucleic acids substantially contributes to their structural flexibility. To model nucleic acid structure and dynamics correctly, the potentially sampled substates of the sugar-phosphate backbone must be properly described. However, because of the complexity of the electronic distribution in the nucleic acid backbone, its representation by classical force fields is very challenging. In this work, the three-dimensional potential energy surfaces with two independent variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 135 publications
1
87
1
1
Order By: Relevance
“…In response, a re-examination of the α/γ torsional behaviour in ff99 was carried out based on refined quantum chemical studies of the relevant part of the DNA backbone, resulting in the modification to ff99 now known as parmbsc0 (Perez et al 2007a, b; Svozil et al 2008). This was a non-trivial undertaking, since not only the behaviour of the α/γ torsional needs to be corrected but extensive testing is required to make sure other errors were not inadvertently introduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response, a re-examination of the α/γ torsional behaviour in ff99 was carried out based on refined quantum chemical studies of the relevant part of the DNA backbone, resulting in the modification to ff99 now known as parmbsc0 (Perez et al 2007a, b; Svozil et al 2008). This was a non-trivial undertaking, since not only the behaviour of the α/γ torsional needs to be corrected but extensive testing is required to make sure other errors were not inadvertently introduced.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, transitions in the DNA backbone of the γ backbone torsion angle to trans , transitions that should be reversible (Varnai et al 2002), were found to accumulate and eventually degrade the duplex structure. Considerable effort was required to correct this problem properly (Perez et al 2007a, b; Svozil et al 2008) and the whole set of simulations was rerun, this time at the level of 50 ns trajectories. This is referred to as ABC II and is described in an article that appeared in 2010 (Lavery et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[33] An experimental assignment of the g torsion angle using H4'-H5' and H4'-H5'' coupling constants and NOEs was not possible since the H5' and H5'' signals could not be assigned.…”
Section: Analysis Of the Sugar-phosphate Backbonementioning
confidence: 99%
“…During these systematic investigations of the sequence dependence of tetrameric repeats in DNA, we learned about artifacts from anomalous α,γ transitions bringing γ to trans (fixed by parmbsc0) [64] and salt crystal formation at abnormally low concentrations [49,65]. Further improvements to the force fields in Amber removed “ladder-like” structures in RNA helices [6669] and may improve ε/ζ backbone states in DNA [70]. Similar improvements in the CHARMM force fields for RNA and DNA have been published [71,72].…”
Section: Introductionmentioning
confidence: 99%